First‐In‐Human, First‐In‐Class, Phase I Trial of the Fucosylation Inhibitor SGN‐2FF in Patients with Advanced Solid Tumors. (22nd September 2021) - Do, Khanh T.; Chow, Laura Quan Man; Reckamp, Karen; Sanborn, Rachel E.; Burris, Howard; Robert, Francisco; Camidge, D. Ross; Steuer, Conor E.; Strickler, John H.; Weise, Amy; Specht, Jennifer M.; Gutierrez, Martin; et al.
Abstract: Lessons Learned: Inhibition of glycoprotein fucosylation, as monotherapy and in combination with immune checkpoint blockade, is a promising therapeutic strategy for treating a broad range of cancers. In this first‐in‐human, first‐in‐class, phase I study in advanced solid tumors, SGN‐2FF demonstrated dose‐proportional pharmacokinetics, evidence of pharmacodynamic target inhibition of glycoprotein fucosylation, and preliminary antitumor activity. SGN‐2FF was associated with thromboembolic events that led to study termination. Background: We conducted a first‐in‐human, first‐in‐class, phase I study of SGN‐2FF, a potent small‐molecule inhibitor of glycoprotein fucosylation, in patients with advanced solid tumors. Methods: The study consisted of four parts: SGN‐2FF monotherapy dose‐escalation (part A) and expansion (part B), and SGN‐2FF + pembrolizumab dose‐escalation (part C) and expansion (part D). The objectives were to evaluate safety and tolerability, maximum tolerated dose (MTD), pharmacokinetics (PK), pharmacodynamics (PD), and antitumor activity of SGN‐2FF monotherapy and SGN‐2FF + pembrolizumab. Results: Forty‐six patients were enrolled (part A, n = 33; part B, n = 6; part C, n = 7; part D did not enroll any patients). During part A ( n = 32) exploring 1–15 g once daily (QD) and 2–5 g twice daily (b.i.d.), grade 3 dose‐limiting toxicities were diarrhea (2 g and 15 g QD) and increased lipase (2 g QD). The MTD was 10 g daily. In part A, common toxicities were grades 1–2 diarrhea, fatigue, and nausea (each 47%); thromboembolic events (grades 2–5) occurred in 5 of 32 patients (16%). Safety measures included concurrent prophylactic anticoagulation with low‐molecular weight heparin (LMWH). In part C, despite the safety measures implemented, a thromboembolic event occurred in one of seven patients (14%) during the SGN‐2FF lead‐in period. Of 28 evaluable patients in part A, 1 patient with advanced head and neck squamous cell carcinoma achieved Response Evaluation Criteria in Solid Tumors (RECIST) v1.1 complete response (CR) and 10 (36%) had RECIST v1.1 stable disease, including 1 patient with advanced triple‐negative breast cancer with 51% tumor burden reduction. SGN‐2FF administration led to dose‐proportional increases in exposure and PD reduction in protein fucosylation. Conclusion: SGN‐2FF demonstrated proof‐of‐mechanism and preliminary antitumor activity but was associated with thromboembolic events leading to study termination.